(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
In this study, hydroxyapatite (HAp) and gelatin (GEL) scaffolds were prepared to mimic the mineral and organic component of natural bone. The raw material was first compounded and resulting composite were molded into the petridishes. Using Solvent casting process, it is possible to produce scaffolds with mechanical and structural properties close to natural trabecular bone.The mechanical properties of composites were investigated by Thermo-mechanical analyzer (TMA), Vickers microhardness tester, Universal testing machine. It was observed that the composite has maximum tensile strength of 37.13MPa ( oven drying) and % elongation of 7.68 (Oven drying) and 2.04 (Natural drying) at 15% of Hap respectively. These results demonstrate that the prepared composite scaffold is a potential candidate for bone tissue engineering. Bangladesh J. Sci. Ind. Res. 50(1), 15-20, 2015